Jalan Raya Pos dan Jalan Daendels: Infrastruktur Kolonial dalam Perspektif Pacem in Terris - Prasetyo , Paulinus Herlambang (Parahyangan Catholic University, 2024)
The digital era triggers an anthropology crisis of the body. This is marked by the emergence of views on the objectification of the body and the commodification of sexuality, where the human body is reduced to an object of consumption and exploitation. Phenomena such as pornography, body image culture, and unrealistic beauty standards obscure the spiritual meaning of the body as a divine creation. These issues lead to a degradation of understanding regarding the values of marriage, sexuality, and human relationships. This study aims to examine the relevance of John Paul II’s Theology of the Body as a solution to these phenomena. John Paul II's teachings, rooted in a profound reflection on the Scriptures, position the body as a medium for revealing love and self-giving. The body is not merely understood as a biological reality but also as a spiritual and transcendent dimension that reflects God's love. Through concepts such as the spousal meaning of the body and humanity’s call to live in purity of heart, the Theology of the Body offers a holistic and profound perspective on the body, sexuality, and human relationships. This study employs a literature review method, analyzing 129 catecheses of John Paul II alongside various modern social phenomena. The findings demonstrate that the Theology of the Body restores the dignity of the human body by opposing objectification and exploitation while promoting loving relationships that are dignified and sacred. By understanding the body as a sacrament of love that reflects the human identity as God’s image, John Paul II’s Theology of the Body serves not only as a theological solution but also as a practical response to social, cultural, and moral challenges in the modern era.